PENGARUH NON PERFORMING LOAN (NPL) TERHADAP PROFITABILITAS - Agustami, Silviana; Moris Wirekso, Antoni (Jurnal Riset Akuntansi dan Keuangan, 2013)
Profitability is one of the essential elements in the process of assessing performance in banking finance. Bank needs to keep its profitability to maintain the continuity of its corporation. In the process of attaining income and making profit, a bank commonly does many efforts. One of them is through offering the credits to the public. However, in fact, credit which becomes the basis to run the company has the risk of failure when the clients/ debtors have to pay the loan back on its deadline/ Non Performing Loan (NPL). The objective of this study is to find out whether NPL influences negatively or not towards the bank profitability.This study employed the basic regression analysis method through linearity and normality tests. The data used is the financial statement of PT. Bank OCBC NISP, Tbk in 2002 until 2010 published by Bank Indonesia.Based on the revealed elaboration and the data analysis about the influence of NPL towards profitability, it can be concluded that the condition of Non-Performing Loan (NPL) in PT. Bank OCBC NISP, Tbk is good in general since it is still below the NPL value regulated by Bank Indonesia which is 5%. Meanwhile, the profitability based on the return on assets (ROA) in PT. Bank OCBC NISP tends to be below the minimum standard which is 1,5%, but it is classified in high category in the framework of performance determination of banking finance governed by Bank Indonesia. In PT. Bank OCBC NISP, Tbk, Non-Performing Loan (NPL) influences negatively towards profitability.